Gratitude experience of nursing students during final stage of clinical internship: A qualitative study from the perspective of positive psychology (积极心理学视角下护理实习生实习后期感恩体验的质性研究) - NIAN Guihong (年桂红); LI Qiaomei (李巧梅); ZHANG Ting (张婷) (中西医结合护理)
Objective To deeply investigate the Gratitude experience of nursing students during final stage of clinical internship, and provide reference for establishment of Gratitude intervention program. Methods Twelve nursing student who participated in the clinical internship were recruited using a purposive sampling method, A face-to-face semi-structured method was adopted, and qualitative data was analyzed Colaizzis method of phenomenological analysis. Results Four themes were indentified: Attitude towards the nursing profession; Inspiration of gratitude; Improvement of critical thinking and adaptability to changes; Improvement of professional self-identity and sense of fulfillment. Conclusion The Gratitude was considered as an important positive psychological experience. Efforts should be made to elicit the underlying feelings of gratitude of students and then turn it to positive attitudes. Meanwhile, nursing students’ needs should be taking into consideration for developing specialized, individualized and high-quality teaching service. (目的 深入了解护理实习生实习后期的感恩心理体验, 为护理管理人员制定感恩干预方案提供理论依据。方法 采用目的抽样的方法选取2021年10月—2022年7月在上海市某三甲医院实习的12名护理实习生为研究对象, 通过质性研究的现象学研究方法对其进行面对面的半结构式访谈, 并用Colaizzi7步分析法对资料进行分析, 提炼主题。结果 通过分析总结出4个主题: 正视护理专业态度; 激发感激之情; 提高思维方式和应变能力; 提高职业认同感和获得感。结论 感恩是护理实习生一项重要的积极心理体验, 临床教学工作中护理工作者应充分激发实习生自身潜在的感恩情绪并将其转化为一种积极的力量, 以促进实习生身心健康, 提高实习质量的同时重视实习生的需求, 制订更加专业、个性化、优质的教学服务。)